Psychologia terrorysty w zwierciadle Fiodora Dostojewskiego (Świat Idei i Polityki, 2005)
In recent years terrorism has gathered strength. However, it is not a new phenomenon. In Europe, its beginning goes back to the mid-19th century. Since that time terrorism has undergone evolution. The definition of terrorism causes many problems. Its beginning in Russia was described by Fyodor Dostoyevsky in his .The Devils.. Basing on the novel, one may get an impression that terrorists are people specifically shaped by social and cultural circumstances. At the same time, terrorism becomes a method of fighting which is not connected with one ethnic or religious formation. The terrorists. vision of the world is black and white and clear-cut. The specificity of terrorist methods authorizes to psychological and sociological characteristic of a terrorist. It is both a community and individual features that determine a terrorist. Considering the fact that terrorism dramatically challenges the present social order, it should be submitted to discussion as far as the values practiced by a society and the political system functioning are concerned. Terrorism requires moral assessment and the choice between utilitarianism and ethic absolutis.